Large Small compressible and Large Small retractable Modules - Khaleel Ibrahim, Rawnaq; M. Yassen, Sahira (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
We consider R is any ring with identity and  is a non-zero unitary left R-module. In this article we introduce the notion of large small Compressible modules and large small Retractable module. Also, we will discuss and study many basic properties about these concepts with its generalization to the ring. Where a submodule  of  is said to be large small of  denoted by if for  such that  then  is essential in .